1970
DOI: 10.3329/bmj.v40i1.9958
|View full text |Cite
|
Sign up to set email alerts
|

Light Emitting Diode (LED) Fluorescent Microscopy: a Milestone in the Detection of Paucibacillary Mycobacterium in Case of Pulmonary Tuberculosis

Abstract: In Bangladesh with a large number of pulmonary tuberculosis cases and financial constraints with high HIV risk, evaluation of scanty i.e paucibacillary cases has great importance. To study the efficacy of Light Emitting Diode fluorescent microscopy in the diagnosis of pulmonary tuberculosis specially paucibacillary cases in comparison to conventional fluorescent microscopy, Ziehl-Neelsen staining and culture of sputum samples from patients suspected of pulmonary tuberculosis. 150 sputum samples collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
1
4
1
Order By: Relevance
“…In our study, the specificity ZN stained microscopy is 95.28% which is almost similar to the findings reported from Bangladesh specificity (97.61%) and Ethiopia (specificity of (96.5%)) ( [12,13]. When this finding is compared to the previous study results (91.3%) reported by Rahman and his colleagues, the specificity is higher [14].…”
Section: Discussionsupporting
confidence: 81%
“…In our study, the specificity ZN stained microscopy is 95.28% which is almost similar to the findings reported from Bangladesh specificity (97.61%) and Ethiopia (specificity of (96.5%)) ( [12,13]. When this finding is compared to the previous study results (91.3%) reported by Rahman and his colleagues, the specificity is higher [14].…”
Section: Discussionsupporting
confidence: 81%
“…Smear microscopy, the most widely available TB diagnostic test has poor sensitivity [ 2 ]. Sputum culture, the gold standard has a long turnaround time (up to 42 days) [ 3 ], whereas the recently developed GeneXpert MTB/RIF test (Cepheid Inc., Sunnyvale, USA), although rapid, is expensive, amongst other limitations which hamper its use in resource-poor countries [ 4 ]. All these tests also depend on the quality of sputum provided by the patient, to yield reliable results.…”
Section: Introductionmentioning
confidence: 99%
“…Golia S et al 14 proved that fluorescent staining was more efficient over ZN staining in determining paucibacillary pulmonary tuberculosis cases. Khatun Z et al 34 reported that only 4% cases of grade scanty were detected by ZN whereas LED fluorescent microscopy detected 14.67% cases. Thus Khatun Z et al 34 declared that fluorescent microscopy is a better method than ZN staining due to its close comparability to the gold standard culture technique.…”
Section: Grade Wise Distribution Of Smearsmentioning
confidence: 99%
“…Khatun Z et al 34 reported that only 4% cases of grade scanty were detected by ZN whereas LED fluorescent microscopy detected 14.67% cases. Thus Khatun Z et al 34 declared that fluorescent microscopy is a better method than ZN staining due to its close comparability to the gold standard culture technique. Studies by Golia S et al 14 and Khatun et al 34 noted that more paucibacillary cases were detected by fluorescent microscopy as compared to ZN light microscopy.…”
Section: Grade Wise Distribution Of Smearsmentioning
confidence: 99%
See 1 more Smart Citation